Optimizing Student Learning Outcomes Through the Jigsaw Type Cooperative Learning Model Assisted by Mind Mapping Media - Antara, I Kadek Nika; Wibawa, I Made Citra; Sukmana, Adrianus I Wayan Ilia Yuda (Journal for Lesson and Learning Studies, 2024)
The low learning outcomes of science are due to the current science learning process, which still applies teacher-centered teaching methods as a material provider. The learning process uses the lecture method, which only requires students to learn science by memorizing concepts, theories, and laws. This study aims to analyze the effect of the Jigsaw-type cooperative learning model assisted by Mind mapping media on science learning outcomes of grade IV students. This study included quasi-experimental research with a research design of a non-equivalent post-test-only control group design. The population of this study was all fourth-grade students, totalling 167 students. The sample of this study was taken using a random sampling technique or a lottery technique. The data analyzed in this study were the science learning outcomes of students whose learning outcomes data collection methods used the test method with multiple choice test sets. Data analysis techniques in this study used descriptive statistical analysis techniques and prerequisite test analysis (t-test). The results of calculating the average (mean) of science learning outcomes of experimental group students with very high criteria, while the average (mean) value of students in the control group with high categories. Thus, the Jigsaw-type cooperative learning model assisted by Mind mapping media significantly affects the science learning outcomes of grade IV students.